2021
DOI: 10.1038/s41526-021-00147-7
|View full text |Cite
|
Sign up to set email alerts
|

Bone health in spacefaring rodents and primates: systematic review and meta-analysis

Abstract: Animals in space exploration studies serve both as a model for human physiology and as a means to understand the physiological effects of microgravity. To quantify the microgravity-induced changes to bone health in animals, we systematically searched Medline, Embase, Web of Science, BIOSIS, and NASA Technical reports. We selected 40 papers focusing on the bone health of 95 rats, 61 mice, and 9 rhesus monkeys from 22 space missions. The percentage difference from ground control in rodents was –24.1% [Confidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 58 publications
5
26
0
Order By: Relevance
“…The systematic searches were performed on Medline, Embase, PubMed, BIOSIS Previews, and Web of Science using the search strategy reported in Fu, Goldsmith et al 13 . Additionally, 9 articles were identified from other sources including the NASA Technical Reporting Service and articles referenced in the compendium of NASA’s animal and cell spaceflight experiments compiled by Ronca et al 12 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The systematic searches were performed on Medline, Embase, PubMed, BIOSIS Previews, and Web of Science using the search strategy reported in Fu, Goldsmith et al 13 . Additionally, 9 articles were identified from other sources including the NASA Technical Reporting Service and articles referenced in the compendium of NASA’s animal and cell spaceflight experiments compiled by Ronca et al 12 .…”
Section: Resultsmentioning
confidence: 99%
“…Following title and abstract screening, 1159 were determined to be concerning animals sent to space. Previously, we identified that a majority of bone health-focused animal studies reported findings in mice, rats and primates (348 articles) 13 . In this study, we performed the full text screening of the these articles and identified 54 articles 14 – 66 that contained quantitative measures of bone strength, bone mineral density (BMD) and composition (included parameters are presented in Table 1 and Supplementary Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations